2001
DOI: 10.3354/dao047175
|View full text |Cite
|
Sign up to set email alerts
|

Detection of infectious salmon anaemia virus (ISAV) by RT-PCR after cohabitant exposure in Atlantic salmon Salmo salar

Abstract: A reverse transcription polymerase chain reaction (RT-PCR) was used to study the early phase of infectious salmon anaemia virus (ISAV) infection in Atlantic salmon Salmo salar L. The detection threshold for the RT-PCR was estimated to be 0.01 to 0.1 TCID 50 . A protocol that closely mimics the conditions in populations of farmed salmon was used. The major port of ISAV entry was most likely the gills, but oral entry could not be excluded. The gills and heart were RT-PCR positive 5 d post infection and there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 16 publications
2
55
0
Order By: Relevance
“…This indicates that the virus has only a single peak viremic period, and that fish that survive this period survive the infection. However, some authors 31 reported a second peak viremic period that resulted in 100% mortality within the same infected group. A bimodal peak of mortality is also believed by some authors 31 to be the result of a second round of infection from the high levels of virus shed by fish that were initially infected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that the virus has only a single peak viremic period, and that fish that survive this period survive the infection. However, some authors 31 reported a second peak viremic period that resulted in 100% mortality within the same infected group. A bimodal peak of mortality is also believed by some authors 31 to be the result of a second round of infection from the high levels of virus shed by fish that were initially infected.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors 31 reported a second peak viremic period that resulted in 100% mortality within the same infected group. A bimodal peak of mortality is also believed by some authors 31 to be the result of a second round of infection from the high levels of virus shed by fish that were initially infected. This is more frequently seen with waterborne or cohabitation challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR method is a more sensitive method than tissue culture for diagnosing ISAV (Devold et al 2000, Mikalsen et al 2001, this issue) and, therefore, was chosen for confirmation of whether mortality could be attributed to ISA. The deaths of the 2 fish that tested negative by RT-PCR could not be attributed to ISAV and were not included in further analysis.…”
Section: Infected Fishmentioning
confidence: 99%
“…The major target cells for virulent ISAV are endothelial cells lining blood vessels of all organs, including sinusoids, endocardium and endothelial macrophages [44][45][46]. The gills are assumed to be the major port of virus entry, but oral entry cannot be excluded [47,48]. Non-virulent ISAV with a HE of the HPR0 variant is often found to present in the gills and to a lower extent in other organs.…”
Section: Pathogenesismentioning
confidence: 99%